2020
DOI: 10.1099/jmm.0.001204
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bactericidal activity of a carbohydrate polymer with zinc oxide for the treatment of chronic wounds

Abstract: Introduction. Biological adhesives and effective topical therapeutic agents that improve wound healing are urgently required for the treatment of chronic ulcers. A biodegradable adhesive based on a carbohydrate polymer with zinc oxide (CPZO) was shown to possess anti-inflammatory activity and enhance wound healing, but its bactericidal activity was unknown. Aim. To investigate the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The groups of microorganisms that usually affect pressure ulcer wounds are Staphylococcus epidermidis, Enterococcus, Streptococcus and Corynebacterium. Being Staphylococcus aureus and Pseudomonas aeruginosas the most common bacterias in pressure ulcers [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The groups of microorganisms that usually affect pressure ulcer wounds are Staphylococcus epidermidis, Enterococcus, Streptococcus and Corynebacterium. Being Staphylococcus aureus and Pseudomonas aeruginosas the most common bacterias in pressure ulcers [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The use of this medical device therefore can be applied in the treatment of diabetic ulcers, chronic varicose venous ulcers and other chronic wounds. CPZO is well tolerated, has not produced any undesirable effects, is easy to prepare and apply at home and does not require refrigeration for storage nor transportation [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups including ours, have reported the clinical finding that when patients with chronic leg ulcers were cared for at home in the manner just described, the prognosis is much improved, better compliance with the treatment, better nutrition, and healing times are reduced as are the family expenses which is extremely important when it is known that many chronic leg ulcers, are frequently experienced by families in lower social levels [3][4][5]. Previous reports have shown that the P.P.Z.O., has potent anti-inflammatory effects and reduces infiltrate of several pro-inflammatory cells, such as mononuclear cells in experiments carried out in in vivo murine models and also, antimicrobial properties even in cases where the responsible causative agent is a multi-resistant bacterium to the most commonly prescribed antimicrobials used everywhere [6].…”
Section: Discussionmentioning
confidence: 99%